Short-term results of ileal pouch anastomosis in early and late terms after urgent surgery for complicated ulcerative colitis - Yu. E. Kitsenko; S. K. Yefetov; I. A. Tulina; P. V. Tsarkov (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
Aim of investigation. To estimate short-term results of ileal pouch anastomosis after urgent colon surgery at complicated ulcerative colitis. Material and methods. Two peer groups including 26 patients each after multi-stage surgical treatment were analyzed. In the first group of patients ileal pouch was created in less than 12 month after primary resection operation, in the second - in more than 12 months. Results. No statistically significant differences between groups were found by any of short-term result scores (p>0.05), including operation time (p=0.48) and volume of blood loss (p=0.88). No significant differences in morbidity rate were found at any stage, including the rate of ileal pouch-anal anastomosis incompetence (p=1.0). Conclusions. Technically ileal pouch anastomosis can be created both several months or several years after colectomy. Time span from subtotal colectomy performance before ileal pouch does not influence short-term treatment results.